Silica microcapsules from diatoms as new carrier for delivery of therapeutics. (September 2011) - Aw, Moom Sinn; Simovic, Spomenka; Addai-Mensah, Jonas; Losic, Dusan
Aim: This study explores the use of natural silica-based porous material from diatoms, known as diatomaceous earth, as a drug carrier of therapeutics for implant- and oral-delivery applications.Materials & Methods: To prove this concept, two drugs models were used and investigated: a hydrophobic (indomethacin) and hydrophilic (gentamicin).Results & Discussion: Results show the effectiveness of diatom microcapsules for drug-delivery application, showing 14–22 wt% drug loading capacity and sustained drug release over 2 weeks. Two steps in the drug release from diatom structures were observed: the first, rapid release (over 6 h is attributed to the surface deposited drug) and the second, slow and sustained release over 2 weeks with zero order kinetics.Conclusion: These results confirm that natural material based on diatom silica can be successfully applied as a drug carrier for both oral and implant drug-delivery applications, offering considerable potential to replace existing synthetic nanomaterials.